The Effect of Resource Complementarity on a Company's Performance Post-Merger and Acquisition in the Southeast Asia Region: The Moderating Role of the Merger and Acquisition Experience - Prayogi, Joni (2022)
This study examines the effect of resource complementarity on a post-merger and acquisition company's performance, moderated by the bidder's merger and acquisition experience. Resource complementarity is an important aspect that needs to be considered when carrying out mergers and acquisitions (M&A). This study uses a purposive sampling method, which has specific criteria for selecting the sample, while the dataset is cross-sectional. Tests have been conducted on 97 non-financial companies that carried out M&A in Southeast Asia between 2007 to 2017, and their post-M&A performance has been examined. This research’s methodology utilizes a quantitative approach and explanatory variables. The results indicate that resource complementarity has a significant effect on the performance of post-M&A companies. In other words, resource complementarity has a positive and significant effect on changes in the performance of companies after their M&A. The moderation test shows exciting findings, namely, for companies with little experience, the effect of resource complementarity on post-M&A performance is more substantial. This study has practical recommendations for decision-makers. When conducting their M&A, organizations should select targets with complementary resources and not depend on prior experience, since it is not necessarily applicable to the present circumstances. Furthermore, as they integrate feedback systems to relate earlier experiences, the acquisition experience will have a more robust learning impact. © 2022, Gadjah Mada University. All rights reserved.